PENGARUH KINERJA KEUANGAN, KEBIJAKAN MONETER DAN PANDEMI PADA PEMBIAYAAN UMKM BANK UMUM - Al Wafi, Ali Daffa; Hascayani, Tyas Danarti (Contemporary Studies in Economic, Finance and Banking, 2023)
MSMEs, one of the crucial sectors of the economy in Indonesia, are experiencing a downturn due to a decrease in the financing needed to deal with a pandemic. This research aims to find the relationship between banking financial performance, monetary policy, and the pandemic on MSME financing. Financial performance is described using the ratio of return on assets, operating expenses to operating income, and third-party funds while monetary policy uses BIrate as the variable and then for a pandemic uses a dummy variable starting from the date the pandemic status was established in Indonesia. The research method used is the multiple regression method with monthly time series data types from January 2018 to April 2022. This research shows results in the form of bank financial performance which strongly influences MSME financing. However, the pandemic did not have much impact on MSME financing, this could happen due to the resilience of MSMEs. As for the BIrate, it shows an anomaly where the decrease in the BIrate is followed by a reduction in MSME financing.